Engajamento de estudantes e seus preditores: estudo em uma instituição federal de ensino - Gomes, Leonardo Cardoso (2020)
In marketing literature, customer engagement is a relatively new concept, but one that is growing in interest both by researchers and professionals in the field. In the educational sector, educational institutions are increasingly recognizing the value of establishing productive relationships with students and obtaining student loyalty and engagement, thereby fostering the development of teaching and the active participation of IES (I Higher Education Institution ) in the academic and social formation of the student. The study sought to analyze some factors considered in the literature as predictors of student engagement in the context of the Federal Institute of Santa Catarina (IFSC), for this purpose, five specific objectives were established, namely: a) to identify the level of student engagement with institution; b) assess whether satisfaction is a predictor of student engagement; c) examine whether trust is a predictor of student engagement; d) identify whether commitment (affective and calculative) is a predictor of student engagement and e) assess whether the quality of educational services is a predictor of student engagement. In addition to the established objectives and after analyzing the literature, four hypotheses were established to guide this work, linked to the mooring matrix, student engagement, which are: H1: Satisfaction has a positive effect on student engagement; H2: Commitment has a positive effect on student engagement; H3: Trust has a positive effect on student engagement and finally H4: The quality of educational services has a positive effect on student engagement. This research is a quantitative, descriptive study in the form of a field survey, involving students enrolled in undergraduate courses. Data were collected through a self-administered questionnaire, made available on the Google Docs platform, where there were 381 respondents, from all IFSC campuses. In order to measure the research results, the frequency analysis of the responses was carried out and, in sequence, the adoption of the Structural Equation modeling for the analysis of the research hypotheses, which were analyzed, according to the verification of the path coefficients and t test. , thus, also, with the reliability analysis of the applied model. After the analysis, all the factorial loads obtained, referring to the latent variables of the factors were higher than the limit of 0.5. Subsequently, the data were analyzed with the aid of descriptive statistical techniques and Structural Equation Modeling. At the end of the research, there was a high degree of student engagement with the HEI studied, as well as allowing the H1 hypotheses to be validated; H2 and H3, thus, the results show a positive relationship between the research constructs, except for the quality of educational services has a positive effect on student engagement on the results. The study stands out for addressing the topic of student engagement in the Brazilian context and within a federal educational institution, and contributed to the identification of predictive factors for student engagement, a theme with a lack of studies.